IMPLEMENTASI UNDANG UNDANG NOMOR 6 TAHUN 2014 TENTANG DANA DESA DI PENTADIO TIMUR KECAMATAN TELAGA BIRU - Mohi, Widya Kurniati; Hulalata, Dian (Program Studi Akuntansi, 2021)
This research aims to determine how the implementation of Law Number 6 of 2014 concerning Village Funds in East Pentadio, Telaga Biru District and the use of the Village Fund Budget for the prosperity and welfare of the village community in East Pentadio Village, Telaga Biru District, with a qualitative descriptive research method with The data collection technique is done by using the data collection technique through interviews, observation, and documentation. In this study, it can be seen that from four indicators, namely Communication, Resources, Disposition, Bureaucratic Structure to measure the implementation of Law Number 6 of 2014 concerning Village Funds at Pentadio Timur, Telaga Biru District, it can be concluded that all variables are good even though there are still mistakes. One variable that looks unfavorable is: The bureaucracy structure meets the standards but currently shows that there are still disparities in carrying out organizational duties and functions in policymaking